PENGARUH KESADARAN WAJIB PAJAK, PEMERIKSAAN PAJAK DAN KETEGASAN SANKSI PAJAK TERHADAP KEPATUHAN PENGUSAHA HOTEL DALAM MEMBAYAR PAJAK HOTEL - Suryani, Suryani; Saleh, Muhammad (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
The aim of this research is to examine the influence of tax payers awareness, tax audit and strict tax penalties toward tax compliance of hotel enterpreneurs in paying the hotel tax in Banda Aceh. The method used in this research was survey method by using questionnaires as the research instruments. The samples were chosen randomly, they were a number of 35 hotel enterpreneurs registered in DPKAD Banda Aceh. The data were collected by giving the questionnaires to those enterpreneurs. The data were the analyzed by using multiple linear regression analysis. The results of this research showed that tax payers awareness, tax audit, and tax strict tax penalties simultaneously influenced the compliance of the hotel enterpreneurs. In addition, tax payer awareness, tax audit and strict tax penalties partially infuenced the compliance of the hotel enterpreneurs.